Analisa Sebaran Lapisan Sedimentasi Karbonate Berdasarkan Hasil Index Properties - Akbar Tri Gumilang; Edy Soesanto; Abdullah Rizky Agusman (Jurnal Bhara Petro Energi, 2024)
This island is a sub-district located east of Pulau Laut at position 3° 24′ 23″ N o r t h Latitude and 116° 24′ 21″ East Longitude. The research location can be reached in 10 hours by road from Banjarmasin to Batulicin Ferry Port, the coast to Pulau Laut using the ferry for 2 hours arriving at Tanjung Serdang Port, followed by a land trip on Pulau Laut to Teluk Gosong Pier for 2 hours, the port by speedboat to arrive at Tanjung Nusantara Pier on Sebuku Island. Sebuku Island is included in the geological map of the 1812 Kotabaru Sheet, according to Rustandi (1995) there are four rock formations that make up Sebuku Island, among others (old to young); Ultrabasic Mesozoic Formation, Pitap Formation, Haruyan Formation, Tanjung Formation, and alluvium quaternary deposits. The Pitap Formation is of late Cretaceous age, deposited in a shallow marine environment, with a fairly wide distribution area. Its lithology consists of alternating conglomerates. The total weight of the sample is a factor that influences a carbonate percentage calculation. Water content is a factor that influences a calculated value.